Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4187/respcare.01411
|View full text |Cite
|
Sign up to set email alerts
|

What Does Airway Resistance Tell Us About Lung Function?

Abstract: SummarySpirometry is considered the primary method to detect the air flow limitation associated with obstructive lung disease. However, air flow limitation is the end-result of many factors that contribute to obstructive lung disease. One of these factors is increased airway resistance. Airway resistance is traditionally measured by relating air flow and driving pressure using body plethysmography, thus deriving airway resistance (R aw ), specific airway resistance (sR aw ), and specific airway conductance (sG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 78 publications
(118 reference statements)
4
112
1
2
Order By: Relevance
“…However, measurement of airway resistance (and derived parameters) has not always been viewed as a complement of spirometry. 18 The availability of body plethysmography allows measurement of the pressure drop across the airways and relates this pressure to flow at the mouth. Because lung volume (V TG ) can be measured in the same session, it is useful to express resistance and its reciprocal, conductance, as specific for the lung volume at which they are measured (sR aw and sG aw , respectively).…”
Section: Airway Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…However, measurement of airway resistance (and derived parameters) has not always been viewed as a complement of spirometry. 18 The availability of body plethysmography allows measurement of the pressure drop across the airways and relates this pressure to flow at the mouth. Because lung volume (V TG ) can be measured in the same session, it is useful to express resistance and its reciprocal, conductance, as specific for the lung volume at which they are measured (sR aw and sG aw , respectively).…”
Section: Airway Resistancementioning
confidence: 99%
“…These include the FOT, 18 enhanced use of transcutaneous P O 2 and P CO 2 sensors (for adults as well as children), uptake of NO to measure D LNO (membrane transfer factor), 44 impedance cardiography to measure cardiac output, 19 and analysis of exhaled NO (F ENO ) to assess airway inflammation. 35 Some technologies are on the horizon that are "brand new" and may have a role in the PFT lab of the future.…”
Section: Pft Lab Of the Futurementioning
confidence: 99%
“…We have previously shown that as early as age 3 years, sRaw differs between children with a history of wheezing and those without (9), and higher sRaw at age 3 years is associated with subsequent persistence of wheezing (14). In childhood, sRaw is considered to be independent of age, height, and sex, thus facilitating the interpretation of longitudinal measurements in individual subjects (5,8,12,13). Previous data from our group indicated a possible increase in sRaw through early childhood (14).…”
mentioning
confidence: 99%
“…For younger children, the techniques that can be performed during tidal breathing are more practical (7). One such method is measurement of specific airway resistance (sRaw) using plethysmography (8)(9)(10)(11)(12)(13), which can be a useful measure in clinical practice and research studies (11). We have previously shown that as early as age 3 years, sRaw differs between children with a history of wheezing and those without (9), and higher sRaw at age 3 years is associated with subsequent persistence of wheezing (14).…”
mentioning
confidence: 99%
“…1 Moreover, deep inhalation is thought to maintain airway smooth muscle homeostasis and to possess bronchodilating and bronchoprotective properties against challenge agents. [2][3][4][5][6] The bronchodilatory effect of deep inhalation is clearly impaired in asthma patients 2,7,8 ; however, the bronchoprotective properties of deep inhalation against challenge test agonists (eg, methacholine) remain robust in many asthma patients with mild airway hyper-responsiveness.…”
Section: Introductionmentioning
confidence: 99%